2004
DOI: 10.1124/jpet.104.075887
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Interactions between the Muscarinic Cholinergic and Dopaminergic Systems in the Modulation of Prepulse Inhibition in Rats

Abstract: Prepulse inhibition (PPI) of the acoustic startle reflex is a sensorimotor gating process known to be deficient in a number of neurologic and psychiatric conditions, including schizophrenia. Multiple lines of evidence have indicated that the dopaminergic and muscarinic cholinergic systems play an important role in modulating PPI. Moreover, interactions between the dopaminergic and muscarinic cholinergic systems are well known; however, little is known about potential interactions between the two systems in mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
3
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 32 publications
6
56
3
1
Order By: Relevance
“…Other animal data that support such a premise are evident in a recent study in which PPI deficits induced by immunolesions of cholinergic neurons of the nucleus basalis were reversed by the AChEI, rivastigmine (Ballmaier et al, 2002). Additional data to support the role of muscarinic receptors in PPI (and that these receptors could serve as targets for drug development in schizophrenia) have been reported in a recent study in which, xanomeline, an M 1 /M 4 AChR agonist (Jones et al, 2005;Stanhope et al, 2001), normalized apomorphine-reduced PPI levels.…”
Section: Discussionmentioning
confidence: 79%
“…Other animal data that support such a premise are evident in a recent study in which PPI deficits induced by immunolesions of cholinergic neurons of the nucleus basalis were reversed by the AChEI, rivastigmine (Ballmaier et al, 2002). Additional data to support the role of muscarinic receptors in PPI (and that these receptors could serve as targets for drug development in schizophrenia) have been reported in a recent study in which, xanomeline, an M 1 /M 4 AChR agonist (Jones et al, 2005;Stanhope et al, 2001), normalized apomorphine-reduced PPI levels.…”
Section: Discussionmentioning
confidence: 79%
“…Animal studies support both dopamine-dependent and dopamine-independent effects of muscarinic agents. 40,190 The muscarinic and dopaminergic system interact bidirectionally at different levels in the brain and the nature of these interactions is not fully understood. Depending on the brain region and muscarinic receptor subtype involved, stimulation and inhibition of the muscarinic system can result in different effects on the dopaminergic system.…”
Section: Discussionmentioning
confidence: 99%
“…189 Both BuTAC and xanomeline reverse a pharmacological disruption of the PPI in a way similar to dopamine D 2 -antagonists. 190 Sarter et al 191 recently suggested that an abnormal increase in the reactivity of the cholinergic neurotransmission results in an impaired regulation of the mesolimbic dopaminergic neurotransmission and thus in the symptoms of schizophrenia. It should be kept in mind that these effects are not unidirectional, as the release of dopamine also has an effect on the regulation of the muscarinic cholinergic system.…”
Section: Use Of Cholinesterase Inhibitors In Schizophreniamentioning
confidence: 99%
“…51 In summary, We propose that the attenuation of phosphoinositide hydrolysis due to the absence of PLC-b1 and feedback mechanisms regulating plasticity of muscarinic receptor expression in the adult neocortex may be responsible for the reduction of pirenzepine binding in standard housed KO animals. Muscarinic signaling has been demonstrated to modulate, and to be modulated by, other signaling systems, including dopaminergic 52 and GABAergic pathways. [53][54][55] More specifically, the observed phenotypes may be elicited as a result of decreased M1 receptor expression mediating an increase in striatal extracellular dopamine, as observed in the M1 KO mouse, 53 resulting in the impaired motor and sensorimotor phenotype recorded for these animals.…”
Section: Discussionmentioning
confidence: 99%